Changes in the approach of polish journalists’ use of social media caused by the Covid-19 pandemic - Gawronski, Slawomir; Tworzydło, Dariusz; Tomczak, Jakub (Penerbit Universiti Kebangsaan Malaysia, 2022)
The article aims to identify and define the changes that are taking place in the approach of Polish journalists to the use of social media and forms of communication between journalists and PR specialists, taking into account changes related to COVID-19. The research in the area of methodology development, tool design, implementation of the adopted assumptions, and report preparation was carried out by the Polish Press Agency in Warsaw (PPA - polish state news agency) and the authors. The result of the survey is 316 questionnaires completed by journalists. During analyses, CATI research was used. The presented results are representative of the journalistic community and allow for extrapolation to the entire population of journalists and media workers in Poland. It was found that the importance of information and its consumption had increased. The situation related to the COVID-19 pandemic has significantly changed the work of Polish journalists publishing their content on social media, which results directly from the significant changes that have affected this medium. An increase in the speed of its spread was also observed. These factors negatively affect the quality of information and its credibility, resulting in fake news. The article presents tools supporting journalists in the fight against disinformation and fake news - which were particularly intense during the COVID-19 pandemic.